A successful multidisciplinary approach for treatment and for preserving the reproductive potential in a rare case of acute lymphocytic leukemia during pregnancy. (1st February 2019) - Salama, Mahmoud; Isachenko, Evgenia; Ludwig, Sebastian; Einzmann, Thomas; Rahimi, Gohar; Mallmann, Peter; Isachenko, Vladimir
Abstract: Leukemia in pregnancy is a rare condition with the prevalence of 1 in 75, 000–100, 000 pregnancies. In this case report, we present a successful multidisciplinary management strategy for treatment and for preserving the reproductive potential in a rare case of acute lymphocytic leukemia (ALL) during pregnancy. Several complex challenges existed and necessitated a multidisciplinary approach with strong coordination and collaboration between oncologists, gynecologists, reproductive cryobiologists, obstetricians, and neonatologists in order to improve the maternal and fetal outcome. Pregnancy in the second trimester is neither a contraindication for ALL treatment nor for emergency fertility preservation via ovarian tissue extraction and further cryopreservation.